Study of the cumulative ability of Ficus nitida trees for some heavy metal elements in the city of Jableh (Syria) - هاجر ناصر; كامل خليل; سليم محمود (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to estimate the concentration of heavy metals: Lead (Pb), Cdmium (Cd), Copper (Cu), Nickel (Ni) and Zinc (Zn) in the leaves of Ficus nitida trees in the city of Jableh during the spring and autumn seasons of 2020. Leaves samples were collected from five locations (S1, S2, S3, S4 & S5), varying according to traffic density. The concentration of the elements was estimated by an atomic absorption spectrophotometer. The results showed that the order of elemental concentrations (general average) in (ppm) in leaves of Ficus nitida trees was lower in spring: Zn (24.24) > Cu (18.48) > Ni (9.06) > Pb (0.95) > Cd (0.09) compared with autumn: Zn (25.24) > Cu (22.53) > Ni (12.50) > Pb (1.33) > Cd (0.11). The results showed that the values of the elements were within the normal limits except for the element Ni and Cu. The site S3 (bus station) was generally characterized by high values for all elements, especially in the autumn season. A significant positive correlation was also recorded between the elements Pb & Cd and between Cd & in the spring season only. The Metal Accumulation Index (MAI) recorded in the autumn season a value of (8.34), and this supports the proposal to adopt Ficus nitida tree as a bioaccumulator to estimate the pollution resulting from heavy metal elements.